Gamifying tax learning: RPGT interactive game for effective tax education / Norhayati Sulaiman - Sulaiman, Norhayati; Khair Anwar, Irda Syahira; Shamsudin, Siti Marlia; Mansor, Norul Akma; Abdul Wahab, Roslan (Universiti Teknologi MARA, Kedah, 2023)
Studying tax courses, such as Real Property Gains Tax (RPGT), can present notable challenges for students. One of the main hurdles encountered in tax courses is the complexity and technicality of tax laws and regulations. RPGT, with its intricate calculations and numerous components, can be particularly daunting. Traditional teaching methods often rely on theoretical explanations and static examples, which can fail to engage students effectively. As a result, students may struggle to grasp the practical application and implications of RPGT. RPGT interactive game attempts to address these challenges by infusing the learning experience with gamification elements. RPGT is suitable for gamification since it is a stand-alone topic and requires the students practice the application of knowledge, and therefore selected for this innovation project. By incorporating RPGT concepts into interactive games, students will be drawn into an enjoyable and immersive environment. The RPGT interactive game was thoughtfully designed to align with the specific learning objectives of the RPGT topic within a tax course. This gamified approach would enhance engagement, as students can actively participate in decision-making, strategize their approaches, and see the consequences of their choices. From survey conducted for this study, most of the respondents (95%) agreed that the game is able to improve their level of understanding and increase their knowledge regarding the RPGT. The interactive nature of the games fosters a sense of excitement and challenge, increasing student motivation and interest in learning RPGT. This innovative approach has the potential to revolutionize tax education, making it more accessible, enjoyable, and effective for students.